2018
DOI: 10.1002/jcb.27279
|View full text |Cite
|
Sign up to set email alerts
|

Identification of diagnostic biomarker in patients with gestational diabetes mellitus based on transcriptome‐wide gene expression and pattern recognition

Abstract: Gestational diabetes mellitus (GDM) is becoming a growing threat for all pregnancies. In this study, we set up an automatic screening method combining both transcriptomic databases and support vector machine (SVM)-based pattern recognition to select biomarkers that can be used in predicting and preventing GDM for gravidas. We screened 63 samples (32 GDM samples and 31 normal controls) in GEO database for the GDM-specific biomarkers. Differentially expressed genes between patients with GDM and normal controls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Therefore, early diagnosis and personalized medical intervention of GDM are of great significance. Previously, Wang et al [41] has established a diagnostic model by using six gene expression profiles, but the AUC was relatively low. In this study, the SVM was used which based on 10 hub genes for GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early diagnosis and personalized medical intervention of GDM are of great significance. Previously, Wang et al [41] has established a diagnostic model by using six gene expression profiles, but the AUC was relatively low. In this study, the SVM was used which based on 10 hub genes for GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al carried out a bioinformatics analysis based on a gene expression profile from GDM samples. Consequently, they established a promising screening approach for GDM and multiple members of human leukocyte antigen (HLA) superfamily were associated with GDM 7 . Deng et al 8 pointed out that antigen processing pathway and immune‐associated genes played key roles in GDM progression according to an integrated analysis of gene expression and methylation data which was generated from visceral omental adipose tissue of numerous Chinese pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that SVM is widely used in the prognosis and diagnosis of multiple diseases such as cancer and diabetes mellitus [29][30][31]. Moreover, it has been revealed that SVM is applied in the investigation of diagnostic markers in GDM patients based on transcriptome-wide gene expression [32]. However, the practices of SVM models in the identification of CpG methylation biomarkers in the diagnosis of GDM remain unreported.…”
Section: Introductionmentioning
confidence: 99%